2017
DOI: 10.21273/hortsci11092-16
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of Plant Growth Regulators on Callus and Somatic Embryogenesis Induction in Four Elite Theobroma cacao L. Genotypes

Abstract: The effect of plant growth regulators on callus and somatic embryogenesis induction in four Cocoa (Theobroma cacao) genotypes was studied. Flower explants were harvested early in the morning and cultured on Driver and Kuniyuki Walnut (DKW) medium supplemented with 1 mg·L−1 of five auxins type (2,4 dichlorophenoxyacetic acid (2,4-D), 3,4 dichlorophenoxyacetic acid (3,4-D), 2,4,5 trichlorophenoxyacetic acid (2,4,5-T), 4-amino-3,5,6-trichloropicolinic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 8 publications
5
16
1
2
Order By: Relevance
“…Indeed, both combinations have favored embryogenesis from the petals. These results are in agreement with those of Kouassi et al (2017a) who used the auxin/Kin system and Issali et al (2008) who used the auxin/TDZ system. However, other authors (Li et al, 1998;Tan and Furtek, 2003) obtained a better embryogenic response with staminodes using auxin/TDZ system.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, both combinations have favored embryogenesis from the petals. These results are in agreement with those of Kouassi et al (2017a) who used the auxin/Kin system and Issali et al (2008) who used the auxin/TDZ system. However, other authors (Li et al, 1998;Tan and Furtek, 2003) obtained a better embryogenic response with staminodes using auxin/TDZ system.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies as well as this one reported that petals were more embryogenic than staminodes. This is consistent with the C1 genotype (Kouassi et al, 2017a). The best response observed in the petals indicates that both auxins/cytokinins systems, namely auxin/Kin and auxin/TDZ, did not induce embryogenesis differently.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other beneficial modifications to SE media have been reported recently by Kouassi et al . () and Modeste et al . ().…”
Section: Introductionmentioning
confidence: 85%
“…Plant growth regulators and optimization of their proper dosages are also very important for success in in vitro culture (Kouassi et al, 2017;Bhattacharjee and Islam, 2014;Morshed et al, 2014). The somatic and gametic embryogenesis on major cereal crops report that regeneration capability depends on genotype (Ksia et al, 2008;Islam et al, 2001).…”
Section: Introductionmentioning
confidence: 99%